EFEKTIVITAS MODEL DISCOVERY LEARNING BERBASIS DIGITAL TERHADAP PEMAHAMAN KONSEP MATERI SISTEM PENCERNAAN - Ihda Salma Dafira; Wahono Widodo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
The research objective was to determine the effectiveness of the digital-based discovery learning model (powerpoint and video animation learning) on students' concept undestanding of digestive system material. This type of research is Pre-Experimental Design. The research design used is the One Group Pretest - Posttest. This research was conducted at SMP Negeri 60 Surabaya. The sample in the study consisted of two groups, namely the experimental group (VII-H) using a digital-based discovery learning model and the control group (VIII-F) using the commonly applied model. Each group consists of 25 students. The data collection method is the test method given before and after the implementation of the digital-based discovery learning model on digestive system material. The data from pretest dan posttest were then analyzed using N-gain to describe the categories of increasing students' conceptual undestanding. In this study, there were differences in the n-gain results in the two groups that had been applied treatment. Digital-based discovery learning models result in greater improvement than a typical classroom teaching. The results showed an increase of 68% including in the medium category in the experimental group. Annother case in the control group there was an increase of 18%, including the low category. Thus it can be concluded that this digital-based discovery learning model is effectively used in students' concept undestanding to improve the digestive system material in SMP Negeri 60 Surabaya.